Quality characteristics of pleurotus sajor-caju powder: study on nutritional compositions, functional properties and storage stability - Ng, Sze Han; Wan Amir Nizam Wan Ahmad,; Wan Rosli Wan Ishak, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Pleurotus sajor-caju (PSC) is an oyster mushroom widely consumed in Asian countries and successfully cultivated in Malaysia. This study aimed to determine nutritional compositions, functional properties and storage stability of PSC powder based on storage temperature. Fresh PSC was dried using low heat air blow technique and ground into fine powder. Nutritional analyses of PSC powder were conducted following AOAC methods. Functional properties were also determined accordingly. For storage stability study, four portions of PSC powder were stored at temperature of -20, 4, 25 and 35oC separately, and then studied parameters were investigated at time 0, 3 and 6 months. PSC powder contains appreciable amounts of protein (22.41%), ash (7.79%), dietary fibre (56.99%) and β-glucan (3.32%) but low content in sucrose (0.19%) and fat (2.30%). It also possesses notable functional properties such as water holding capacity, oil holding capacity, swelling capacity and emulsifying activity. Storage stability study showed that PSC powder exhibited lower moisture content and L* colorimetric value. Meanwhile higher water activity level with increasing storage temperature but no significant difference in pH value and microbial counts were detected. Besides, storage temperature at -20, 25 and 35oC jeopardized the original colour properties of PSC powder. The best storage temperature for PSC powder is 4oC. PSC powder has the potential to be a safe and as an alternative dietary fibre rich ingredient in food industry due to its nutritional, functional and storage stability properties.